2016
DOI: 10.7196/sajbl.2016.v9i1.465
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising the role of the gatekeeper in social science research

Abstract: Accessing research participants within some social institutions for research purposes may involve a simple single administrative event. However, accessing some institutions to conduct research on their data, personnel, clients or service users can be quite complex. Research ethics committee chairpersons frequently field questions from researchers wanting to know when and why gatekeeper permission should be sought. This article examines the role and influence of gatekeepers in formal and organisational settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 22 publications
1
59
0
1
Order By: Relevance
“…Whilst acknowledging the autonomous power of gatekeepers at support groups and religious organisations to either hinder or promote access to their members or contacts (Singh & Wassenaar, ), there is need to also consider how this may possibly impact on the voluntary rights of potential participants to personally decide their participation or otherwise in a research study (Mamotte & Wassenaar, ; Wanat, ). Experience with participants in this study suggests that they may be willing to participate in research studies if they are asked, as many of them seemed to view their participation as a way of “helping others.” Although the researcher offered to volunteer at one of the support groups approached and all the support groups were also told they would be provided with summary of research findings as an “incentive” for their cooperation (Singh & Wassenaar, ), this strategy remained unsuccessful for the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst acknowledging the autonomous power of gatekeepers at support groups and religious organisations to either hinder or promote access to their members or contacts (Singh & Wassenaar, ), there is need to also consider how this may possibly impact on the voluntary rights of potential participants to personally decide their participation or otherwise in a research study (Mamotte & Wassenaar, ; Wanat, ). Experience with participants in this study suggests that they may be willing to participate in research studies if they are asked, as many of them seemed to view their participation as a way of “helping others.” Although the researcher offered to volunteer at one of the support groups approached and all the support groups were also told they would be provided with summary of research findings as an “incentive” for their cooperation (Singh & Wassenaar, ), this strategy remained unsuccessful for the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence such men did not give their partners the opportunity to make their own informed decision to participate or not. Whilst acknowledging the autonomous power of gatekeepers at support groups and religious organisations to either hinder or promote access to their members or contacts (Singh & Wassenaar, 2016), there is need to also consider how this may possibly impact on the voluntary rights of potential participants to personally decide their participation or otherwise in a research study (Mamotte & Wassenaar, 2017;Wanat, 2008). Experience with participants in this study suggests that they may be willing to participate in research studies if they are asked, as many of them seemed to view their participation as a way of "helping others."…”
Section: Gatekeeping Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…DoH managers control access by researchers to provincial health facilities and are among those stakeholders who are likely to use the results of research. 31 Varying notions of ‘valuable’ research in provincial health facilities emerged as a key theme, as reported and discussed below.…”
Section: Aimsmentioning
confidence: 99%
“…For example, application forms for initial review should have questions that will "trigger" researchers to describe their engagement practices in a way that is 'broad and inclusive' (e.g. more than permission from "institutional gatekeepers") [31]. Renewal forms (progress reports) should enable researchers to describe progress in the preceding year, to promote 'sustained' engagement.…”
Section: Discussionmentioning
confidence: 99%